2005
DOI: 10.1037/0882-7974.20.2.220
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults as Adaptive Decision Makers: Evidence From the Iowa Gambling Task.

Abstract: Older adults process emotional information differently than younger adults and may demonstrate less of a negativity bias on cognitive tasks. The Iowa Gambling Task designed by A. Bechara, H. Damasio, D. Tranel, and A. R. Damasio (1997) has been used to examine the integration of emotion and cognition in a risky-choice decision task and may give insight into differences in the decision-making strategies in younger and older adults. Eighty-eight younger adults (18-34 years) and 67 older adults (65-88 years) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
231
3
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(268 citation statements)
references
References 21 publications
23
231
3
6
Order By: Relevance
“…Wood and colleagues (2005) also used the IGT to assess decision-making in younger (18-34 year old) and older (65-88 year old) adults. While Wood et al (2005) did not report any significant age-related differences in advantageous decisions, the mean performance for older adults was non-significantly lower than that of younger adults and older adults used different strategies than younger adults when learning the task. Finally, MacPherson and colleagues (2002) reported no significant differences in advantageous decision-making between younger and older adults; however, as pointed out by Denburg et al (2005), older adults had generally flatter learning curves compared with younger adults, which seems to suggest some impairment in the ability to learn to make more advantageous decisions over time.…”
Section: Introductioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Wood and colleagues (2005) also used the IGT to assess decision-making in younger (18-34 year old) and older (65-88 year old) adults. While Wood et al (2005) did not report any significant age-related differences in advantageous decisions, the mean performance for older adults was non-significantly lower than that of younger adults and older adults used different strategies than younger adults when learning the task. Finally, MacPherson and colleagues (2002) reported no significant differences in advantageous decision-making between younger and older adults; however, as pointed out by Denburg et al (2005), older adults had generally flatter learning curves compared with younger adults, which seems to suggest some impairment in the ability to learn to make more advantageous decisions over time.…”
Section: Introductioncontrasting
confidence: 61%
“…In addition, Denburg did not find any associations between the IGT and performance on cognitive tests, while we reported an association with the average z-score across all nine cognitive domains assessed. Furthermore, Wood et al (Wood et al, 2005) found that older and younger adults employ different cognitive strategies in regards to decisionmaking as assessed by the IGT. Analyses of our participants also revealed that different cognitive processes are associated with decision-making in older versus younger adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outros autores, no entanto, não aleatorizam os baralhos (e.g. Davis, Patte, Tweed, & Curtis, 2007;Wood, Busemeyer, Koling, Cox, & Davis, 2005), alegando ausência de impacto significativo no desempenho do efeito de ordem ABCD (Stout, Rodawalt, & Siemers, 2001).…”
Section: Aleatorização Espacial Dos Baralhosunclassified
“…For instance, automatic processes may impede deliberation on important factors such as the credibility and relevance of information (e.g., has a piece of medical information come from a physician or a tabloid?). Wood et al 47 suggest that lack of insight into automatic processes in some older adults may make these individuals less attentive to negative emotion or affect signaling red flags (e.g., scams) and result in less loss aversion. Older adults may be less socially vigilant when evaluating the intentions and abilities of physicians and salespeople.…”
Section: Feelings Help Integrate Informationmentioning
confidence: 99%